Smaller Left Ventricle Size at Noncontrast CT Is Associated with Lower Mortality in COPDGene Participants - Washko, George R. (Radiology, 2020)
BACKGROUND: Smokers with chronic obstructive pulmonary disease (COPD) have smaller left ventricles (LVs) due to reduced preload. Skeletal muscle wasting is also common in COPD, but less is known about its contribution to LV size. PURPOSE: To explore the relationships between CT metrics of emphysema, venous vascular volume, and sarcopenia with the LV epicardial volume (LV(EV)) (myocardium and chamber) estimated from chest CT images in participants with COPD and then to determine the clinical relevance of the LV(EV) in multivariable models, including sex and anthropomorphic metrics. MATERIALS AND METHODS: The COPDGene study (ClinicalTrials.gov identifier: NCT00608764) is an ongoing prospective longitudinal observational investigation that began in 2006. LV(EV), distal pulmonary venous blood volume for vessels smaller than 5 mm(2) in cross section (BV5), CT emphysema, and pectoralis muscle area were retrospectively extracted from 3318 nongated, unenhanced COPDGene CT scans. Multivariable linear and Cox regression models were used to explore the association between emphysema, venous BV5, pectoralis muscle area, and LV(EV) as well as the association of LV(EV) with health status using the St George’s Respiratory Questionnaire, 6-minute walk distance, and all-cause mortality. RESULTS: The median age of the cohort was 64 years (interquartile range, 57–70 years). Of the 2423 participants, 1806 were men and 617 were African American. The median LV(EV) between Global Initiative for Chronic Obstructive Lung Disease (GOLD) 1 and GOLD 4 COPD was reduced by 13.9% in women and 17.7% in men (P < .001 for both). In fully adjusted models, higher emphysema percentage (β = –4.2; 95% confidence interval [CI]: –5.0, −3.4; P < .001), venous BV5 (β = 7.0; 95% CI: 5.7, 8.2; P < .001), and pectoralis muscle area (β = 2.7; 95% CI: 1.2, 4.1; P < .001) were independently associated with reduced LV(EV). Reductions in LV(EV) were associated with improved health status (β = 0.3; 95% CI: 0.1, 0.4) and 6-minute walk distance (β = –12.2; 95% CI: –15.2, –9.3). These effects were greater in women than in men. The effect of reduced LV(EV) on mortality (hazard ratio: 1.07; 95% CI: 1.05, 1.09) did not vary by sex. CONCLUSION: In women more than men with chronic obstructive pulmonary disease, a reduction in the estimated left ventricle epicardial volume correlated with a loss of pulmonary venous vasculature, greater pectoralis muscle sarcopenia, and lower all-cause mortality. © RSNA, 2020 Online supplemental material is available for this article.